Peran Istri sebagai Pencari Nafkah dalam Keluarga Modern Perspektif Hukum Ekonomi Islam - Paisal Paisal; Hidayat Hidayat; Saru Reza Reza (Journal of Legal Sustainability, 2026)
This study aims to analyze the wife's role as breadwinner in modern families from the perspective of Islamic economic law. The increasing involvement of women in economic activities indicates a shift in family roles influenced by economic factors, education, and increasingly complex living needs. This study employed a normative legal research method with a qualitative approach through library research. Data sources were obtained from the Quran, Hadith, the Compilation of Islamic Law, Islamic jurisprudence books, and various relevant journals and literature. Data analysis was conducted using content analysis and the maqasid sharia approach. The results show that Islamic economic law does not prohibit wives from working and earning income as long as these activities comply with sharia principles. However, the primary obligation to provide a living remains with the husband. The wife's income is private property, the use of which is based on mutual consent and agreement for the benefit of the family. From the perspective of maqasid sharia, the wife's role as breadwinner can bring benefits by helping to improve family welfare, maintain livelihoods, and meet household economic needs. Therefore, a wife's involvement in earning a living is acceptable under Islamic economic law as long as it maintains family harmony and Sharia values.